Shadow vigilantes: how distrust in the justice system breeds a new kind of lawlessness - Robinson, Paul H. (Prometheus Books, 2018)
Fear, meet indifference: breaching the social contract -- The moral vigilante -- The shadow vigilantes -- Sparking the shadow vigilante impulse -- Ten rules for the moral vigilante -- Moral vigilantes breaking bad: community drug wars -- How being right can risk wrongs -- Community complicity with vigilantes -- The community as shadow vigilantes -- Criminal justice officials as shadow vigilantes -- Blowback and the downward spiral -- The damages and dangers of the community perceiving the system as being indifferent to doing justice -- What it takes to stop the vigilante echo